Both short-and long-term treatment with the direct AMP kinase activator PXL770 improves cardiac function in ZSF-1 rats. (14th October 2021) - Stephan, Y; Souille, M; Larcheveque, M; Gluais-Dagorn, P; Hallakou-Bozec, S; Nicol, L; Mulder, P
Abstract: Introduction: AMPK is a central energy sensor with cardioprotective effects, and its activation has emerged as a target for the treatment of metabolic syndrome-related cardiac dysfunction. PXL770 is the first direct AMPK activator under clinical development, currently investigated for the treatment of NASH. Since potential cardiac benefits of PXL770 have not been previously assessed we investigated whether short- and long-term PXL770 treatment exerts protective cardiac effects in rats with metabolic syndrome. Methods: ZSF-1 rats were treated with PXL770 (150 mg/kg orally BID for 90 days initiated at the age of 12 weeks, or for 7 days initiated at the age of 23 weeks) in order to determine left ventricular (LV) function and remodeling. Results: After 90 days, untreated ZSF-1 rats showed signs of LV diastolic dysfunction, illustrated by the increase in LV end-diastolic pressure (LV EDP; 5.58±0.57 and 8.28±1.02 mmHg in lean and ZSF-1 rats, respectively; p<0.05) and in LV end-diastolic pressure volume-relation (LV EDPVR; 1.10±0.23 and 5.44±0.65 mmHg/RVU in lean and ZSF-1 rats, respectively; p<0.05) with preserved LV systolic function, illustrated by the slight decrease in LV fractional shortening (LV FS; 46±1 and 42±1% in lean and ZSF-1 rats, respectively; p<0.05) and similar LV end-systolic pressure (LV ESP; 173±10 and 197±6 mmHg, respectively) or LV end-systolic pressure volume-relation (LV ESPVR; 32.7±4.2 to 28.6±1.4 mmHg/RVU, respectively). LV diastolic dysfunction was associated with a significant increase in LV tissue collagen density (2.62±0.17 and 4.03±0.13%, respectively) without an alteration in LV weight (1.27±0.02 to 1.22±0.03 g; respectively) Short- and long-term treatment with PXL770 improved LV diastolic function in treated ZSF-1, illustrated by the reduced LV EDP (5.34±0.93 and 5.98±0.94 mmHg, short- and long-term PXL770, respectively) and the reduced LV EDPVR (3.31±0.43 and 2.73±0.16 mmHg/RVU, respectively; p<0.05 vs untreated ZSF-1). Simultaneously LV FS was significantly increased (52±1 and 50±1%, respectively; p<0.05 vs untreated ZSF-1), as well as LV ESPVR (34.6±1.4 and 33.0±0.9 mmHg/RVU, respectively; p<0.05 vs untreated ZSF-1). The improvement of diastolic function was associated with a reduction in LV weight (1.19±0.04 and 1.17±0.02 g, respectively; long-term PXL770 p<0.0.5 vs untreated ZSF-1) and a significant reduction in collagen density after long-term PXL770 (3.35±0.12%; p<0.05) but not short-term PXL770 (4.22±0.30%). Conclusion: These results suggest that PXL770 exerts protective effects on cardiac function and structure in developing or established cardiomyopathy. Thus, by directly activating AMPK, the PXL770 appears promising for the treatment of cardiac dysfunction associated with metabolic diseases. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Poxel SA